Magnetic Ionogel and Its Applications - Sayan Ganguly; Shlomo Margel (Gels)
Magnetic ionogels, a category of hybrid materials consisting of magnetic nanoparticles and ionic liquids, have garnered significant interest owing to their remarkable attributes, including tunability, flexibility, and reactivity to external magnetic fields. These materials provide a distinctive amalgamation of the benefits of both magnetic nanoparticles and ionogels, resulting in improved efficacy across many applications. Magnetic ionogels may be readily controlled using magnetic fields, rendering them suitable for drug administration, biosensing, soft robotics, and actuators. The capacity to incorporate these materials into dynamic systems presents novel opportunities for the development of responsive, intelligent materials capable of real-time environmental adaptation. Nonetheless, despite the promising potential of magnetic ionogels, problems persist, including the optimization of the magnetic particle dispersion, the enhancement of the ionogel mechanical strength, and the improvement of the long-term stability. This review presents a comprehensive examination of the syntheses, characteristics, and uses of magnetic ionogels, emphasizing significant breakthroughs and persistent problems within the domain. We examine recent advancements and prospective research trajectories aimed at enhancing the design and efficacy of magnetic ionogels for practical applications across diverse fields, including biomedical uses, sensors, and next-generation actuators. This review seeks to elucidate the present status of magnetic ionogels and their prospective influence on materials science and engineering.